Ab initio quantum transport in AB-stacked bilayer penta-silicene using atomic orbitals. Issue 59 (3rd October 2018) - Chatzikyriakou, Eleni; Karafiloglou, Padeleimon; Kioseoglou, Joseph
Abstract : A methodology for parameter-free calculations of current density from first-principles using density functional theory, Wannier functions and scattering matrices is presented. The methodology is used on free-standing AB-stacked bilayer penta-silicene. Abstract : The current carried by a material subject to an electric field is microscopically inhomogeneous and can be modelled using scattering theory, in which electrons undergo collisions with the microscopic objects they encounter. We herein present a methodology for parameter-free calculations of the current density from first-principles using density functional theory, Wannier functions and scattering matrices. The methodology is used on free-standing AB-stacked bilayer penta-silicene. This new Si allotrope has been proposed to have a higher stability than any of its hexagonal bilayer counterparts. Furthermore, its semiconducting properties make it ideal for use in electronic components. We unveil the role of the p z orbitals in the transport through a three-dimensional quantum wire and present current density streamlines that reveal the locations of the highest charge flow. The present methodology can be expanded to accommodate many electron degrees of freedom, the application of electromagnetic fields and many other physical phenomena involved in device operation.